Controlled Levitation of Dust Particles in RF+DC Discharges. Issue 9 (7th October 2015) - Bastykova, N. Kh.; Kovács, A. Zs.; Korolov, I.; Kodanova, S. K.; Ramazanov, T. S.; Hartmann, P.; Donkó, Z.
Abstract: Experiments and particle‐based kinetic simulations were performed to obtain the equilibrium levitation height of dust particles in plane parallel electrode discharges in low pressure argon gas, established by combined RF and DC excitation. The computed values were compared to experimental data. The good overall agreement of the simulation results and the experimental data verifies our gas discharge, dust charging, as well as dust force balance models. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)